THE IMPACT OF GLOBALIZATION ON CULTURAL PROPERTIESAND CIVILIZATIONAL HERITAGE - Huda Abdel Rahim Abdelkader (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2019)
The study deals with the role of the media in the protection of cultural heritage and properties through studying the new media and cultural properties in the shadow of globalization. The research follows the descriptive approach by extrapolating the definition of cultural properties, and the analytical approach to determining the role of the new media in the protection of cultural properties. It consists of the impact of globalization on cultural and civilizational heritage through two axis: New media and globalization and the role of globalization in cultural properties and heritage